Solution-Focused Supervision A Resource-Oriented Approach to Developing Clinical Expertise - Thomas, Frank N. (Springer New York : Imprint: Springer, 2013)
As Solution-Focused (SF) Brief Therapy transformed the clinical world with its powerful present/future orientation and innovative techniques, it is no surprise that its approach should be applied to supervision. By contrast, what is surprising is the lack of consensus on what constitutes good SF supervisory practice. Solution-Focused Supervision fills in the blanks, expanding on the approach and analyzing best practices for a unique "what works and why" guide to the supervisory relationship. Chapters examine how SF supervision differs from more traditional forms, the competencies needed for effective SF supervision, and why the approach is applicable to supervising professionals practicing most models of therapy. Real-life examples show the method at work in a variety of clinical settings. And at the same time, the common myth is laid to rest that any competent therapist can be a successful supervisor. This breakthrough book: Defines SF supervision in the context of systems thinking. Details key aspects of the SF supervision approach, including pragmatism, tentativeness, nonpathology, curiosity, and respect. Illustrates supervision dialogue and techniques with session transcripts from the work of the late Insoo Kim Berg, MSSW. Explores concepts and practices of promoting self-supervision within supervision. Includes extended applications, including parenting evaluations, addictions counseling, pastoral counseling, and more. Features a selection of ready-to-use appendices. Pragmatic and visionary, Solution-Focused Supervision will find an interested audience among mental health clinical and administrative supervisors,as well as professors and researchers in mental health fields. Praise for Solution-Focused Supervision: Solution-Focused Supervision is one of the most significant contributions to the solution-focused literature in a long time. Lots of recent "SF" books are good, useful, and significant; however, each is still ultimately just another book about DOING solution-focused brief therapy. This book moves from doing therapy to supervising therapists and, as such, fills an important gap. The Practices chapter is gold!, and the thorough and helpful exploration of the goal-setting process in supervisionis enough for me to recommend this book to supervision colleagues. Solution-Focused Supervision reflects a quantum leap in solution-focused publications. Michael Durrant Faculty of Education and Social Work, University of Sydney Director, Brief Therapy Institute of Sydney Approved Supervisor, Psychology Board of Australia